Evaluation of a new transperineal ultrasound probe for inter-fraction image-guidance for definitive and post-operative prostate cancer radiotherapy. Issue 3 (March 2016) - Fargier-Voiron, Marie; Presles, Benoît; Pommier, Pascal; Munoz, Alexandre; Rit, Simon; Sarrut, David; Biston, Marie-Claude
Highlights: We compare prostate positioning between intramodality transperineal US and CBCT. This is the 1 st clinical study performed with this US probe. Probe pressure and inter-operator uncertainties are minimized with this probe. We found a strong correlation between the shifts obtained with US and CBCT devices. Unlike transabdominal probe this is a promising device for prostate cancer IGRT. Abstract: Purpose: The aim of this study was to evaluate a new system based on transperineal ultrasound (TP-US) acquisitions for prostate and post-prostatectomy pre-treatment positioning by comparing this device to cone-beam computed tomography (CBCT). Methods: The differences between CBCT/CT and TP-US/TP-US registrations were analyzed on 427 and 453 sessions for 13 prostate and 14 post-prostatectomy patients, respectively. The inter-operator variability (IOV) of the registration process, and the impact and variability of the probe pressure were also evaluated. Results: CBCT and TP-US shift agreements at ± 5 mm were 76.6%, 95.1%, 96.3% and 90.3%, 85.0%, 97.6% in anterior-posterior, superior-inferior and left-right directions, for prostate and post-prostatectomy patients, respectively. IOV values were similar between the 2 modalities. Displacements above 5 mm due to strong pressures were observed on both localizations, but such pressures were rarely reproduced during treatment courses. Conclusions: High concordance between CBCT/CT and TP-US/TP-US localization of prostates or prostatic beds was found in this study. TP-US based prepositioning is a feasible method to ensure accurate treatment delivery, and represents an attractive alternative to invasive and/or irradiating imaging modalities.